Fasciotomia testicular descompressiva na torção do cordão espermático: estudo experimental em ratos - Isabela Passos Pereira Quintaes (2012)
BACKGROUND: Testicular torsion causes irreversible damage in ipsilateral testicles induced by ischemia/ reperfusion injury and compartimental syndrome that develops. The goal of the work is to evaluate the role of decompression fasciotomy with beneficial changes in testis suffered the torsion of the spermatic cord. METHOD: The torsion of the spermatic cord was induced in 40 Wistar pubescent testis for a period of 6 and 12 hours. At the time of distortion, decompression fasciotomy was performed in half of the animals. After 42 days,the testicles were examined macro and microscopically. The statistical method used was the non-parametric test of Mann-Whitney. It was considered as significant value p < 0, 0 50. RESULTS: Variables evaluated were weight, testicular volume and the degree of histological alterations by optical microscopy. Comparing groups without and with fasciotomy, was note that the group of 12:00 hour with fasciotomy had larger volume and weight and better histological classification when compared with the group of 12:00 hour without fasciotomy. There was no difference between the 2 groups of 6 hours. Comparing the groups of 6:00 and 12:00 hours, it was noted that in the group without fasciotomy, the degree of commitment was grater in the group of 12 hour, thanin the group of 6 hour, but the groups with fasciotomy of 6 and 12 hours did not show any differences of the variable analyzed. No significant changes were noted in the contralateral testis. CONCLUSION: Decompression testicular fasciotomy benefited macroscopicand histological aspects of the testicles that suffered by cord twist for a period of 12:00, showing the role of compartimental syndrome in its pathophysiology and the need for its decompression.